Transatlantic space politics competition and cooperation above the clouds - Wang, Sheng-Chih 1979- (Space power and politics, 2013)
"This book examines transatlantic politics through an analysis of 60 years of US-European strategic interaction in space. The significance of space politics for the study of transatlantic relations receives surprisingly little scholarly attention. As a theatre of interaction, transatlantic space politics reflects the vicissitudes of European and US power in the international system. An understanding of space politics is therefore vital in understanding the status and prospect of the transatlantic order. Using established IR theories, the author investigates transatlantic space politics and proposes a theoretical explanation, which is distinct from the conventional wisdom of the transatlantic security community. More specifically, he distinguishes between the constitutive and regulatory effects of the transatlantic security community, an approach rarely employed in other research in the field. Overall, this book suggests not only that the transatlantic institutional pillar requires repair, but also that the ideational factors need to be revitalised in order to consolidate the transatlantic alliance.This book will be of much interest to students of space power, transatlantic politics, strategic studies, foreign policy and IR/security studies in general"-- Provided by publisher.